Pengaruh Supervisi Akademik dan Budaya Sekolah Terhadap Kinerja Guru SD di Kecamatan Pecalungan Kabupaten Batang - Zulianto, Zulianto; Buchori, Achmad; Saputra, Bagus Ardi (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The quality of education at the school level is influenced by teacher performance in carrying out tasks, so that teacher performance is an important guide for achieving educational success. The performance of elementary school teachers in the Pecalungan sub-district, Batang Regency, has several problems including some teachers who do not understand about assessment and are not disciplined in time, the preparation for each lesson is not optimal, the conditioning of students in the class is still lacking, and the teacher needs to improve learning strategies that vary in learning. to create a fun and memorable learning atmosphere for students. The purpose of this study was to determine the effect of academic supervision and school culture on the performance of elementary school teachers in Pecalungan District, Batang Regency. This research method uses quantitative methods with descriptive quantitative types. The population in this study were 170 teachers in the Pecalungan area, Batang Regency. There were 10 school principals and 10 teachers selected from each school. The results of this study indicate that there is a positive and significant influence between academic supervision on teacher performance, there is a positive and significant influence between school culture on teacher performance, and there is a positive and significant influence between academic supervision and school culture simultaneously on teacher performance.